Employment versus Wage Adjustment and the U.S. Dollar - Campa, Jose Manuel; Goldberg, Linda S. (The Review of Economics and Statistics, 2001)
Using two decades of annual data, we explore the links between real exchange rates and employment, wages, and overtime activity in U.S. manufacturing industries. Especially in industries with lower price-over-cost markups, exchange rates have statistically significant effects on industry wages, with the magnitude of these effects rising as industries increase their export orientation and declining as imported input use becomes more important. Exchange rate implications for jobs and hours worked are smaller and less precisely measured. We find a much higher response of overtime wages and overtime hours to transitory exchange rates movements.